Embodying Language in Action The Artistry of Process Drama in Second Language Education - Piazzoli, Erika (Springer International Publishing, 2018)
This book explores embodiment in second language education, sociocultural theory and research. It focuses on process drama, an embodied approach that engages learners' imagination, body and voice to create a felt-experience of the second language and culture. Divided into three parts, it begins by examining the aesthetic and intercultural dimension of performative language teaching, the elements of drama and knowing-in-action. The central part of the book examines issues related to play, emotions, classroom discourse and assessment when learning a language through process drama, in a sociocultural perspective. The third part is an analysis of the author's qualitative research, which informs a subtle discussion on reflective practitioner methodology, learner engagement and teacher artistry. Each chapter includes a drama workshop, illustrating in practice what embodying language in action can look like when working with asylum seekers, adult learners with intellectual disabilities, pre-service teachers, international students and children involved in a Content and Language Integrated Learning (CLIL) programme. A unique combination of theory, research and reflective practice, this book provides valuable insights for teacher/artists, teacher educators and researchers in the fields of performative and sociocultural language learning.